The translator as an activist: reframing conflict in the Arabic translation of Sacco's Footnotes in Gaza. (3rd April 2018) - Dubbati, Barkuzar; Abudayeh, Haneen
ABSTRACT: This article employs narrative theory and discourse analysis to examine the translator's paratextual influences in the Arabic translation of Joe Sacco's graphic novel Footnotes in Gaza . We argue that the Palestinian translator sees himself as an activist who has a mission to reframe his people's cause as a struggle for independence. We locate several patterns of interferences that aim to affect readers' perception of the Palestinians and Israelis in Sacco's recounting of the events of Israel's invasion of the Gaza Strip in 1956. This study shows that the translator's paratexts frame Palestinians as victims of Israeli occupation and heroes in their struggle against it. The translator ideologically embeds himself in the translation as he reinterprets certain representations of characters and historical events which respond to his political affiliations and the expectancy norms of his target Arab readers.